Paris as Real and Fantastic Space in Depiction of E. T. A. Hoffmann and Ch. Baudelaire - N. M. Ilchenko (Tsentr nauchnykh i obrazovatelnykh proektov, 2019)
The article discusses the depiction of Paris in E. T. A. Hoffmann’s novella “Das Frӓulein von Scuderi,” 1818 and in Ch. Baudelaire’s series “Tableaux parisiens,” 1861. It is noted that their authors are united by belief in fantasy as a means of knowledge. The relevance of the study is determined by the special attention of literary studies to the development of urbanism, recognizing the importance of the city phenomenon in the modern literary process. It is shown that the German romantic and the French symbolist poet depict Paris through a close interweaving of the fantastic and the real, their characters feel the influence of a large city, and Paris itself becomes a part of them. Special attention is paid to consideration of the thanatological motifs, their participation in the organization of a literary text. The article presents the results of a comparative analysis of the works by German romantic, who created a myth of the city he wasn’t in, and the Parisian, “leaving” Paris for the sake of exotic countries. The novelty of the study is due to the fact that Paris is considered as a dual space - “the universal capital” and the city of political cataclysms; this kind of “complex” is analyzed at the level of problems and poetics of the works by E. T. A. Hoffman and Ch. Baudelaire. This approach allowed the authors to show in the historical perspective the features of the formation of the Paris myth, in which beautiful dreams and disgusting pictures of death coexist.